PROSES KERJA STERILIZER PABRIK KELAPA SAWIT PTPN IV DOLOK SINUMBAH - kevin pratama hasudungan, kevin pratama hasudungan; Tampubolon, Kevin Pratama; Sianturi, Tambos August (Jurnal Penelitian Teknik Dan Sumberdaya Perairan, 2025)
The sterilization process is a very important initial stage in palm oil processing because it directly affects the quality and yield of the resulting oil. The sterilizer functions to stop the activity of the lipase enzyme, facilitate the release of loose fruit from the bunch, and soften the fruit tissue before further processing. This Field Work Practice (PKL) activity aims to study the palm oil processing process at the sterilizer station, including the working principles, operational parameters, and the effect of sterilization on the quality of Fresh Fruit Bunches (FFB). The methods used in writing this journal are direct observation in the field, interviews with operators, and literature studies related to the palm oil sterilization process. The results of the observations indicate that the sterilization process is carried out using pressurized steam at a certain temperature and time to achieve optimal conditions. Control of pressure, temperature, and boiling time is crucial to the success of the sterilization process. An optimal sterilization process can reduce the level of free fatty acids (FFA) and increase the efficiency of subsequent processing. Thus, the sterilizer station plays a crucial role in maintaining the quality and quantity of the palm oil produced.